Does employee willingness to take risks affect customer loyalty? A moderated mediation examination of innovative behaviors and decentralization. Issue 5 (31st May 2021) - Al-Hawari, Mohd Ahmad; Bani-Melhem, Shaker; Mohd. Shamsudin, Faridahwati
Abstract : Purpose: This study aims to build on the trait activation and interactionist perspective theories to investigate the effect of frontline employees' (FLEs) willingness to take risks on hotel guest loyalty by assessing the mediating role of their innovative behaviors. It also examines whether decentralization strengthens the positive impact of willingness to take risks on innovative behavior and, subsequently, customer loyalty. Design/methodology/approach: The authors collected multilevel data from various sources – hotel FLEs ( n = 183), hotel operation managers ( n = 46) and hotel guests/customers ( n = 266) – from five-star hotels operating in Dubai. Structural equation modeling and PROCESS macro (version 3.5) were used to analyze the data. Findings: The findings showed that willingness to take risks indirectly (via innovative behaviors) affects guest/customer loyalty positively. This effect is strengthened when the hotel is decentralized. Practical implications: This study provides insight into how hotel managers can foster customer loyalty. More specifically, they can do so by establishing employees' innovative behaviors triggered by employees' positive personality traits and by giving employees more autonomy. Originality/value: The present study addresses recent calls to investigate the positive impact of FLEs' personality traits, attitudes and behaviors on customer loyalty.